A efetividade da informação contábil gerada em Unidades Gestoras de recursos da união sediadas em Petrolina-PE e Juazeiro-BA - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
Accounting is the science of asset information. Since 2008, the production of such information in the public sector has undergone significant changes with the implementation of International Standards of Accounting Applied to the Public Sector (NBCASP). Faced with this reality comes a concern as the effective use of accounting information for management decision-making. In this sense, this research aims to examine the effectiveness of accounting information generated in Union Resource Management Units based in the cities of Petrolina, PE and Juazeiro, BA in 2015. In this context identifies the relevant factors related to the effective use of accounting information, clarifying the existing accounting information system in public entities is efficient and effective and examines the level of usefulness of accounting information for decision making in the surveyed units. For this work has descriptive and exploratory nature. As for the research techniques were employed bibliographical, documentary and field research. We used yet pragmatic approach and as data collection tools, questionnaire in Likert scale with five alternatives that have been applied to managers and semi-structured interview was held with the accounting officers of the units studied. To interpret the data, it was used descriptive statistics, multivariate data analysis and content analysis. The results showed that there is effective use of accounting information handled by the Union resources managers concerning their decision making. However, there was disagreement between managers and accountants in the evaluation of some attributes that define the effectiveness of information. It was found that the Integrated Financial Administration System (Siafi) stands out as the main structural system of the federal government and that the accounting information system used by the management units do not fully meet the contemporary requirements of public accounting.
Keywords: Informação Contábil; Sistemas de Informações Contábeis (SIC); Accounting Information; Accounting Information Systems; CIENCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIENCIAS CONTABEIS